Perilaku Penderita Hipertensi dalam Mengontrol Tekanan Darah pada Pandemi Covid-19 - Denita Laura; Erwin; Rismadefi Woferst (Program Studi Akuntansi IKOPIN, 2022)
Primary hypertension can be treated by modifying health behaviors to prevent complications. This research aims to describe the health behavior of patients with primary hypertension in controlling blood pressure during the pandemic covid-19 in the Harapan Raya Public Health Center work area. Methods: This is quantitative research using a descriptive design. The research sample of 84 respondents was taken based on the inclusion criteria using purposive sampling technique. The measuring instruments used are questionnaires and a digital sphygmomanometer. The analysis used is univariate analysis to describe the frequency distribution. Result: The results showed that from 84 respondents, behavior of checks health regularly and follow the advice of health workers regarding treatment were 61.9%, behavior to cope with medication appropriately and regularly 48.8%, behavior to maintain a balanced nutrition 51.2% were not compliant, 41.67% rarely did physical activity, behavior to avoid addictive substances in cigarette smoke 79.76% non-smokers/passive smokers. Conclusion: Based on the 5 health behaviors, there are 3 behaviors that are already good, namely checking health regularly, treating patients with primary hypertension, and avoiding additives cigarette smoke. There are 2 behaviors that are lacking good behavior, maintaining a balanced nutrition and seeking physical activity at home during pandemic covid-19.